Problem Solving Approach in Electrical Energy and Power on Students as Physics Teacher Candidates - Riantoni, C.; Yuliati, L.; Mufti, N.; Nehru, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
In agreement with students’ conceptual understanding, identifying of problem solving is an important part of physics. This article is to identify the approach used by students in solving a physics problem. The subject of the research were students of physics education year 2014 in Jambi University who had joined basic physics class. The instruments used in this research were DIRECT (determining and interpreting resistive electric circuit concept test) (Engelhardt & Beichner, 2004). Based on the result, 34,1% students still used the memory based approach in problem solving, 52,3% of them used no clear approach, 4,5% used structured manner, 6,82% used unstructured manner and only 2,27% students used a scientific approach to solving the problem. The result showed that many students used no clear approach and memory based approach to solve the problem. It mean that they did not use physics concept in solving the problem and generally they only used the equation they memorized related to the problem they ever did before.